Individual Characteristics And The Gateway Hypothesis Among Drug User Patient In Indonesia - Aryo Saloko; Asfi Manzilati (State Islamic University of Sunan Ampel, 2021)
Drug abuse has become severe not just in the world but also in Indonesia. To address this problem, public policies and researcher try to understand the drug use pattern. One of the famous concept in drug use pattern is gatheway hypothesis. The gateway hypothesis refers to the pattern of substance use initiate softer drug lead to the harder drug. However, many literature shows drug use pattern is not just gateway pattern, there is reversal pattern and using both gateway and reversal pattern. Many studies have discussed the relationship between drug use and individual characteristics. However, few of them are relatively link between individual characteristics and the sequential order in drug use. The purpose of this study is to evaluate how individual characteristics are associated with the gateway pattern and other pattern for different types of drugs. We use a secondary dataset of individual drug user patients from the Rehabilitation Center of National Narcotics Board aged 14–67 years assessed using the Addiction Severity Index (ASI), employing probit and multinominal logit model. Duration are associated with initial soft drug user with gateway pattern. While alcohol use and have high education level related with initial hard drug user with reversal pattern. Interestingly, duration and alcohol use correlated with initial intermediate drug user with all kind of pattern. Prevention and intervention efforts should be targeting high-risk characteristics of people at an initial stage of drug use and progression to the next stage.